Return-to-sport criteria after anterior cruciate ligament reconstruction fail to identify the risk of second anterior cruciate ligament injury - Paterno, M. V.; Rauh, M. J.; Thomas, S.; Hewett, T. E.; Schmitt, L. C. (Journal of Athletic Training, 2022)
Background The incidence of second anterior cruciate ligament (ACL) injury after ACL reconstruction (ACLR) is high in young, active populations. Failure to successfully meet return-to-sport (RTS) criteria may identify adult athletes at risk of future injury; however, these studies have yet to assess skeletally mature adolescent athletes.